Spillovers of COVID-19 on Employment and Income in Peru - Tello Pacheco, Mario (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper estimates the spillovers effects of COVID-19 on employment (total, formal, and informal) and real income of a group of Peruvian provinces called “treated or treatment” in the period of the virus 2020- II-2021-IV. These spillovers are associated with the behavior of people who broke the confinement, crowded into relatively small spaces, and did not use protective measures against COVID-19. The measurements of these effects are based on Cao and Dowd (2019), and on the INEI-ENAHO National Household Survey (2022) for the period 2011.I-2021-IV, which is the main database of the study. Two main results of the study are, on the one hand, that COVID-19 and the confinement policies and transfers to the poor and companies contributed on average to more than 50% of the decrease in total employment, formal employment, and real income (of the economically active population employed in the province), and to the increase in informality for the group of provinces covered. On the other hand, the spillovers effects attenuated the negative effects of the decrease in formal employment and real income in said provinces.